Sports massage for athletes target-men - Lance, Carrie (MyMassageVideo.com, 2009)
What is Therapeutic Sports Massage? Therapeutic sports massage is a type of massage technique that focuses on treating soft tissue aches, pains and injuries that are associated with recreationsl activities. You don't have to be in the Olympics to benefit from sports massage. Whether you are an avid skier, or just working off those holiday pounds, a Sports Massage is the perfect way to relax those tight, overworked muscles with a mix of techniques with several sports streches for the problem areas. These areas may include the Hamstrings, Quads, Calf muscles & Glutes.